2008
DOI: 10.11646/zootaxa.1968.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Rediscovery of Gryon chrysolaum (Walker) (Hymenoptera: Platygastridae)—an egg parasitoid of Holhymenia rubiginosa Breddin and Anisoscelis foliacea Fabricius (Heteroptera: Coreidae)

Abstract: During surveys of natural enemies of the leaf-footed bugs Holhymenia rubiginosa Breddin and Anisoscelis foliacea Fabricius in Rio Grande do Sul State, Brazil, two species of primary egg parasitoids belonging to the genus Gryon were reared from these hosts. One of these Gryon species was identified as G. chrysolaum Walker, a species unknown since its description nearly 170 years ago. The second Gryon species reared was G. vitripenne Masner. These rearings represent the first host records for this species. Level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The present paper extends the geographic range of G. vitripenne to Sete Lagoas municipality, Minas Gerais State, Brazil, about 7,600 km SE from Brownsville and Harlingen, Texas, EUA, the types localities (Masner 1983), and about 1,200 km SE from Campo Verde, Mato Grosso State and 1,400 km NE from Porto Alegre, Rio Grande do Sul State, the previously known records in Brazil (Polaszek and Kolberg 2008;Margaría 2008;Margaría et al 2009). Based on the results of this study we have increased the knowledge about the associations and distribution of G. vitripenne, a potential agent of biological control of L. zonatus.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…The present paper extends the geographic range of G. vitripenne to Sete Lagoas municipality, Minas Gerais State, Brazil, about 7,600 km SE from Brownsville and Harlingen, Texas, EUA, the types localities (Masner 1983), and about 1,200 km SE from Campo Verde, Mato Grosso State and 1,400 km NE from Porto Alegre, Rio Grande do Sul State, the previously known records in Brazil (Polaszek and Kolberg 2008;Margaría 2008;Margaría et al 2009). Based on the results of this study we have increased the knowledge about the associations and distribution of G. vitripenne, a potential agent of biological control of L. zonatus.…”
Section: Resultssupporting
confidence: 69%
“…Almost nothing is known about the biology and habits of G. vitripenne: when Masner (1983) described the species he stated that part of the type series was obtained from eggs of an unidentified coreid. Polaszek and Kolberg (2008) reported the primary parasitism of G. vitripenne in Holhymenia rubiginosa Breddin, 1904 and Anisoscelis foliaceus (Fabricius, 1803) (Heteroptera: Coreidae) eggs, Margaría (2008) and Margaría et al (2009) reported that exemplars of G. vitripenne were reared form eggs of unidentified bugs on Oryza sativa (Poaceae).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The wasp species has been recorded parasitizing eggs of Holhymenia rubiginosa Breddin, 1904 (Hemiptera: Coreidae) in passionfruit crops (Paloszeck & Kolberg 2008), eggs of Leptoglossus zonatus Dallas, 1852 (Hemiptera: Coreidae) (Perioto et al 2019) and an undetermined species of mealybugs in rice crops (Margaría et al 2009).…”
Section: Scientific Notementioning
confidence: 99%